1997
DOI: 10.1002/(sici)1098-2795(199701)46:1<62::aid-mrd10>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Relative role of CSF-1, MCP-1/JE, and RANTES in macrophage recruitment during successful pregnancy

Abstract: It has been previously demonstrated that macrophage colony stimulating factor (CSF‐1) is produced by uterine epithelial cells in response to estrogen and progesterone. Studies in normal and op/op mice demonstrated that accumulation of a portion of the uterine macrophage population could be attributed to the chemotactic properties of CSF‐1. Op/op mice exhibit greatly reduced rates of fertility, but successful pregnancy is not completely blocked. Also, uteri from op/op mice are not completely macrophage deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 21 publications
3
54
0
Order By: Relevance
“…Speculatively, high seminal eotaxin and RANTES levels may further operate directly on these eosinophils as they express -at least -an eotaxin-specific receptor which may regulate their selective recruitment (Mould et al 1997). Unlike in man, murine coitus results in the deposition of semen directly into the uterus where, as allogenic material, it triggers an acute inflammatory response (Wood et al 1997). Thus, seminal fluid constituents -potentially including eotaxin, MIP-a, IL-1b and IL-9 -initiate a surge in the synthesis of other cytokines (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Speculatively, high seminal eotaxin and RANTES levels may further operate directly on these eosinophils as they express -at least -an eotaxin-specific receptor which may regulate their selective recruitment (Mould et al 1997). Unlike in man, murine coitus results in the deposition of semen directly into the uterus where, as allogenic material, it triggers an acute inflammatory response (Wood et al 1997). Thus, seminal fluid constituents -potentially including eotaxin, MIP-a, IL-1b and IL-9 -initiate a surge in the synthesis of other cytokines (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…We further detected macrophage chemoattractants, MCP-1 and MIP-la, in the pregnant uterus. The expression of RANTES and MCP-1 has been demonstrated in the pregnant murine uterus (WOOD et al, 1997). These findings suggest that M-CSF and chemokines in combination contribute to the recruitment of macrophages.…”
Section: Discussionsupporting
confidence: 84%
“…A variety of uterine cell types undergo dramatic changes during the course of pregnancy. The number of macrophages increases significantly during this time (WOOD et al, 1997). Similar to inflammation, this macrophage accumulation results in the production of various cytokines in the pregnant uterus (BARTOCCI et al, 1986;ARCECI et al, 1989;ROBERTSON and SEAMARK, 1992;HUNT et al, 1993). Among several macrophage growth factors, the macrophage colony-stimulating factor (M-CSF/CSF-1) plays an important role in the development, differentiation, proliferation, and chemokinetics of macrophages (LADNER et al, 1987;WONG et al, 1989;CECCHINI et al, 1994;METCALF and NICOLA, 1995;WEBB et al, 1996).…”
mentioning
confidence: 99%
“…Several chemokines targeting macrophages and granulocytes are also induced within hours of mating (Wood et al 1997, Pollard et al 1998 and it is likely that these cytokines function synergistically to orchestrate extravasation and spatial positioning as well as the activation phenotypes of inflammatory cells. The current study has suggested that expression of these same pro-inflammatory mediators are induced in the porcine uterus after interaction between seminal plasma and uterine cells, with GM-CSF, IL-6 and MCP-1 each induced after seminal plasma exposure.…”
Section: Pbs Spmentioning
confidence: 99%